PERBANDINGAN METODE MLE BAYESIAN LOSS FUNCTION DALAM PENDUGAAN PARAMETER DISTRIBUSI INVERS RAYLEIGH - Muhammad Iqbal; Ferra Yanuar; Dodi Devianto (LPPM Universitas Bina Bangsa, 2023)
The purposes of this study are to estimate the scale parameter of invers Rayleigh distribution under MLE, Bayesian Generalized square error loss function (SELF), and Bayesian LINEX loss function . The posterior distribution is considered to use two types of prior, namely Jeffrey’s prior and exponential distribution. The proposed methods are then employed in the real data. Several criteria AIC, AICc, and BIC for the selection model are considered in order to identify the method which results in a suitable value of parameter estimated. This study found that Bayesian Generalized SELF at first polynomial and Bayesian LINEX loss function under exponential distribution yielded better estimation values than MLE based on AIC, AICc, and BIC